Bliss effect of taxpayers in adopting blockchain technology - Yenni Mangoting; Priscilla Amanda Setiawan; Elizabeth Nuralim (Journal of Accounting and Investment, 2023)
Research aims: This study aimed to investigate the intention to adopt blockchain technology (BT) from the taxpayer’s perspective.Design/Methodology/Approach: The data were collected from an online survey with 135 effective respondents and analyzed using Partial Least Square (PLS) for model and hypothesis testing.Research findings: It was found that perceived enjoyment could mediate the effect of autonomy on intentions to use blockchain technology in tax administration. However, it has been proven that autonomy had a greater direct effect than the indirect effect of perceived enjoyment as a mediation.Theoretical contribution/Originality: This research discusses how people react to using blockchain technology in the tax administration system. The use of blockchain technology will later have an impact on the transparency and effectiveness of taxation. Practically, from within the taxpayer arises a desire to carry out his obligations using blockchain technology. Blockchain technology is essential to facilitate and increase transparency in the effectiveness of tax administration systems.Practitioner/Policy implication: The findings of this study offer a practical guide for tax authorities as regulators in designing the BT implementation in the tax administration system that will increase transparency and efficiency.Research limitation/Implication: This study has several limitations. First, the model and hypothesis in this study have never been researched as one model. Second, some respondents only have a hazy understanding of how the blockchain works. Hence, future research may be able to broaden the research by investigating the outcomes of blockchain technology adoption.